2003
DOI: 10.1785/0120020033
|View full text |Cite
|
Sign up to set email alerts
|

Aftershocks and Triggered Events of the Great 1906 California Earthquake

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Present-day seismicity is nearly absent on the Shelter Cove part of the northern SAF where the largest coseismic slip is inferred. Based on the analysis of catalogues and reports of felt aftershocks, Meltzner and Wald (59) concluded that there was no large aftershocks on the rupture plane.…”
Section: )mentioning
confidence: 99%
“…Present-day seismicity is nearly absent on the Shelter Cove part of the northern SAF where the largest coseismic slip is inferred. Based on the analysis of catalogues and reports of felt aftershocks, Meltzner and Wald (59) concluded that there was no large aftershocks on the rupture plane.…”
Section: )mentioning
confidence: 99%
“…In the 5 years following the 1857 M W 7.9 Fort Tejon earthquake on the southern SAF, there is no evidence for any M Ն6 aftershocks on the SAF, except for an M ϳ6.2 event that may have occurred on the SAF near or northwest of Parkfield in 1860 (Meltzner and Wald [1999]; Toppozada et al [2000] and have M I 6.0 for this event); in the 20 months following the 1906 M W 7.8 San Francisco earthquake on the locked northern SAF, the only M Ն5.5 aftershock that appears to have been on the SAF was an M 5.6 event near San Juan Bautista one month after the mainshock (Meltzner and Wald, 2003). Note that Parkfield is at the southern boundary of the creeping section of the SAF and has occasionally experienced M ϳ6 events, and that San Juan Bautista is at the northern boundary of the creeping section and has occasionally experienced M ϳ5.5 events (e.g., Hill et al [1990]; Toppozada et al [2000; ).…”
Section: Discussionmentioning
confidence: 91%
“…5). Such elongation of the location contours is not uncommon for historical data sets in California (e.g., Meltzner and Wald, 2003): if the epicentral location is well constrained by observations to the northwest and southeast but it is poorly constrained in the sparsely populated inland region and unconstrained offshore, then the location contours will be elongated in a direction perpendicular to the coastline. In other words, the elongation of those contours to the northeast and southwest is mostly an artifact of the irregular geographic distribution of the intensity data, and it is somewhat fortuitous that the intensity center is so close to the region of known surface rupture.…”
Section: Location and Magnitudementioning
confidence: 89%
“…In one of the simulated scenarios, for example, an M 6.95 occurs east of Sacramento, near the Sierra Nevada, and in another an M 7.2 rips along a parallel trend to the Sierra Madre fault, strongly affecting the San Gabriel Valley, a densely populated region containing over 40 municipalities and about 2 million people. There is clear precedent for such triggering of distant aftershocks by large San Andreas earthquakes; within two days of the 1906 San Francisco San Andreas earthquake, distant aftershocks occurred in or near the Imperial Valley, Pomona Valley, Santa Monica Bay, western Nevada, and western Arizona (Meltzner and Wald 2003); and shortly after the 1857 Ft. Tejon earthquake, additional earthquakes were felt in the northern California cities of Martinez, Benecia, Santa Cruz, San Juan Batista, San Benito, and Mariposa (Townley and Allen 1939). Overall four out of our 10 simulations had one or more M ≥ 5 aftershocks triggered somewhere north of the central California city of Parkfield.…”
Section: Resultsmentioning
confidence: 99%